The Multiple K-Riemann Integral - Oussama Kabbouch; Mustapha Najmeddine (Abstract and Applied Analysis)
The aim of this paper is to extend the notion of K-Riemann integrability of functions defined over a,b to functions defined over a rectangular box of ℝn. As a generalization of step functions, we introduce a notion of K-step functions which allows us to give an equivalent definition of the K-Riemann integrable functions.